The Effect of Canva-Assisted Infographic Learning Media on Students' Conceptual Understanding with Learning Interest as a Moderat - Abdul Razak Sumarandak (Journal of Educational Technology and Innovation, 2026)
Informatics learning in secondary schools continues to face challenges in improving students’ conceptual understanding, particularly of abstract concepts. Although previous studies have demonstrated the effectiveness of infographic media in supporting learning, most have focused on media development or general effectiveness without examining the moderating role of learning interest. Therefore, the novelty of this study lies in investigating the effect of Canva-assisted infographic learning media on conceptual understanding with learning interest as a moderating variable. This study aimed to analyze the effect of Canva-assisted infographic learning media on students’ conceptual understanding in Informatics. A quantitative approach employing a 2 × 2 quasi-experimental factorial design was used involving tenth-grade students at SMA Negeri 2 Gorontalo. The first factor was learning media (Canva-assisted infographic media and conventional media), while the second factor was learning interest (high and low). Data were collected through a conceptual understanding test and a learning interest questionnaire and analyzed using two-way ANOVA. The results showed that Canva-assisted infographic learning media positively affected students’ conceptual understanding and that learning interest significantly moderated this effect. These findings indicate that Canva-assisted infographic media is an effective instructional alternative for enhancing conceptual understanding in Informatics.